2021
DOI: 10.1186/s12877-021-02581-4
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is associated with decreased gray matter volume in the parietal lobe: a longitudinal cohort study

Abstract: Background Substantial evidence supports an association between physical activity and cognitive function. However, the role of muscle mass and function in brain structural changes is not well known. This study investigated whether sarcopenia, defined as low muscle mass and strength, accelerates brain volume atrophy. Methods A total of 1284 participants with sarcopenic measurements and baseline and 4-year follow-up brain magnetic resonance images we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
(54 reference statements)
1
11
1
Order By: Relevance
“…27 Although not specifically indicated the precuneus area, a previous longitudinal study showed that muscle mass is associated with parietal GM volume atrophy, in a middle-aged cognitively normal subjects. 12 Taken these together, our results with precuneus area cortical reduction might be significant aberrant sign of sarcopenia as risk factor of cognitive impairment including AD and other dementia.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…27 Although not specifically indicated the precuneus area, a previous longitudinal study showed that muscle mass is associated with parietal GM volume atrophy, in a middle-aged cognitively normal subjects. 12 Taken these together, our results with precuneus area cortical reduction might be significant aberrant sign of sarcopenia as risk factor of cognitive impairment including AD and other dementia.…”
Section: Discussionsupporting
confidence: 67%
“…A recent previous large longitudinal study with 1,284 cognitively normal participants showed that significantly greater atrophy in parietal area was observed in the sarcopenia group compared with the control group. 12 They also found that low muscle mass, not muscle strength, was an independent factor associated with a decrease of gray matter (GM) volume in a joint regression model. Although they suggested that patients with sarcopenia showed GM volume reductions in the frontal, temporal, and parietal regions and in the subcortical structures when compared with the controls, the results were sometimes rather inconsistent.…”
Section: Cortical Thickness and White Matter Hyperintensity Changesmentioning
confidence: 97%
“…Few studies have evaluated the relationship between this metric and volumetric quantification on MRI. One study of 1,284 participants in the Korean Genome and Epidemiology Study did not find a relationship between handgrip strength and total gray matter volume and parietal lobe gray matter [40]. This study did show a reduction in cognition in persons with sarcopenia defined by low muscle mass.…”
Section: Discussioncontrasting
confidence: 46%
“…This may help explain the increasing trend of grip strength asymmetry with a period. The ageing process of the human body, changes in muscle structure and reduced function [22] , as well as the onset of multiple chronic diseases [23], and neurological damage [24], may all be risk factors for the increasing proportion of people with grip asymmetry. This study suggests that grip asymmetry in older adults accounts for nearly half of the total population in China and should be considered in future studies to assess grip asymmetry.…”
Section: Relationship Grip Asymmetry and Adlmentioning
confidence: 99%